Pengaruh Variabel Makroekonomi terhadap Penyaluran Transaksi Ekspor dan Impor dengan Metode Pembayaran Letter of Credit - Ni Putu Ayuning Wulan Pradnyani Mahayana; Yusman Syaukat; Dwi Rachmina (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
Letter of credit (LC) is one of term of payments on export import transaction. The purpose of this study is to analyze the impact ofmacroeconomic variables changes i.e exchange rate, inflation and the Bank Indonesia (BI) rateto value of LC, with study case in one of Bank in Indonesia.This study also analyze the differences in impact of the commodity on export import by using LC between agricultural and non-agricultural products. The data is analyzed by using Error Correction Model (ECM) to investigate the long run and short run relationship between macroeconomic variables and value of LC over the period of 2013–2016. The result show that the long run relationship between macroeconomic variables changes and value of LC is significant. Over all, the result show that allof the macroeconomic in this study was significantly influence the value of LC export, whereas the value of LC import was not influence by inflation variable. Differences of the commodity on export import by using LC also showing the different impact to the value of LC especially for inflation variable. The value of LC export and import of agricultural products was not influence by inflation variable. The recommendation for the bank to optimize the LC transaction is when domestic currency have depreciation, then the bank can increasethe LC transaction on export side either on agricultural or non-agricultural products. And then for BI rate factor, the bank should be wary of increase of the BI Rate because it can be impact to decrease the LC transaction.